(untitled) (The Research of Medical Science Review, 2025)
Technological advances and new research methodologies have transformed the pharmaceutical sector. Machine learning and artificial intelligence are speeding up everything from hyper automation in drug discovery to clinical trials. Also, new digital health technologies along with gene and cell therapies are improving patient-centered care, adherence to medication, and even patient participatory medicine. In addition to these factors, blockchain technology is anticipated to improve the pharmaceutical supply chain and change the attitude towards environmentally sustainable practices.